The ballad of Ballard and Sandrine - Straub, Peter, 1943- (Subterranean Press, 2011)
Ballard and Sandrine, widely separated in age but bound together by a common erotic obsession, are aboard a yacht making its endless way down the Amazon river. Their journey encompasses moments of beauty and horror, mystery and revelation, pleasure and pain, culminating in the vision of an astonishing-- and appalling-- apotheosis.